A novel method to protect bronze in atmospheric environment: the click-assembly of triazole film. Issue 3 (11th April 2020) - Zhou, Hao; Zhang, Kai; Zhang, Lin; Lu, Jiamin; Li, Jin; Zhang, Daquan; Gao, Lixin
Abstract : Purpose: The authors have prepared the triazole film on copper surface by click reaction and explored its inhibition mechanism. Design/methodology/approach: The protective film is assembled by immersing bronze in solution containing p -toluenesulfonyl azide (TA) and propiolic acid (PA). Findings: Fourier transform infrared spectroscopy (FT-IR) indicates that triazole (TTP) film was formed on bronze surface via click chemistry reaction between TA and PA. It shows TTP film has a good protection for bronze in the atmospheric environment simulation solution. Quantum chemical calculation (QC) and molecule dynamics simulation suggests TTP molecule adsorbs on bronze surface via N and O. Originality/value: This is beneficial to develop the corrosion inhibitors for the corroded copper alloys.